Vitamin C improves 28-day survival in patients with sepsis-associated acute kidney injury in the intensive care unit: a retrospective study - He, Yang; Liu, Jinglan (Frontiers in Nutrition, 2025)
BackgroundVitamin C, a water-soluble essential micronutrient, exhibits multifaceted physiological roles including immune modulation and enhanced resistance to infectious pathogens. Evidence suggests that hypovitaminosis C is associated with adverse clinical outcomes in critically ill populations, with notably high prevalence observed in acute kidney injury patients. This retrospective study aimed to evaluate the potential association between vitamin C supplementation during intensive care unit admission and improved clinical outcomes, specifically in sepsis-associated acute kidney injury (SA-AKI).MethodsUtilizing data from the Medical Information Mart for Intensive Care IV (MIMIC-IV), a repository of ICU patient records from Beth Israel Deaconess Medical Center (United States), we identified patients diagnosed with SA-AKI. Participants were stratified into two cohorts: those receiving intravenous vitamin C supplementation during ICU stay (vitamin C group) and those without supplementation (non-vitamin C group). Primary outcomes, including in-hospital mortality, were evaluated using Kaplan–Meier survival curves, Cox proportional hazards regression models, and subgroup analyses. Propensity score matching (PSM) was employed to mitigate potential confounding. Secondary outcomes encompassed 28-day mortality.ResultsAmong 16,140 patients diagnosed with SA-AKI, 589 received vitamin C supplementation, while 15,551 did not. Kaplan–Meier analysis revealed a significant divergence in survival probabilities between cohorts (log-rank p < 0.001). After adjusting for confounders via Cox regression, the vitamin C group demonstrated a 17% reduction in in-hospital mortality risk (adjusted hazard ratio [aHR] 0.67, 95% CI: 0.57–0.79; p < 0.001). Consistency was maintained across PSM, paired algorithm, and overlap weighting analyses, with all p < 0.001.ConclusionVitamin C supplementation during ICU admission may be associated with reduced in-hospital mortality in SA-AKI patients. These findings underscore the need for prospective randomized trials to validate causality.